The Importance of the Teacher-Student Ratio in Improving the Quality of the Educational Environment in Higher Educational Institutions - Yuldashev Feruz Isroil o’g’li (Global Scientific Publishing, 2023)
Although the 21st century is considered to be a rich period in achievements in various fields of science, unprecedented natural and other types of disasters beyond human control continue to threaten the well-being of society. The experience of developed countries has proven that ensuring the well-being of society depends on the continuous development of science and the productive application of a quality education system. In this article, the importance of the teacher-student ratio in the modern conditions of the higher education system, in the environment of technological development of the society, and the actual conditions of the ratio in countries with a highly developed educational system today are studied. Also, the issues of ensuring the teacher-student relationship at the optimal level in the higher education system of Uzbekistan are studied in the regulatory documents and in practice, and the dynamics of changes in this ratio over the years are analyzed. The results of the article show that in improving the quality of education, it is important for teachers to create the necessary environment in educational processes, and this process explains the need to ensure a directly proportional teacher-student ratio in the fields of education.
Keywords: Remote teaching; traditional classes; teacher-student ratio; labor market